Experience report of medical students according to interprofessional parameters in regional hospital (Research, Society and Development, 2020)
Experience report of not mandatory probation, performed in a regional hospital in a city from Minas Gerais, from January to February, 2020. Objective: After a detailed examination of the following items, the aim of this article was to present the experiences and activities lived during the internship. Method: report of experience. The following data collection techniques were applied: diary stage, structured observation (participant researcher), consultation of medical records, analysis of clinical/managerial activities, verification of the physical structure of the hospital, consultation with public normative and regulatory agencies of health services. Results: It was possible to describe the presence of the multiprofessional team and the clinical profile of patient care, cite the various forms of approaches available and describe some relevant aspects in the new form of group action - interprofessionality. Final Considerations: the experience was significant, signaling that the scenario in question is crucial as a field of dispersion for the student of medicine who seeks to broaden his knowledge and also apply today's principles such as interprofessionalism in the professional and academic spheres.